Фразеологічні одиниці як засіб атракції англомовних газетних заголовків - Sunko, Nataliia; Kinashchuk, Tetiana (Рута, 2021)
The article is devoted to the study of the role of phraseological units in English newspaper headlines. The aim of the work is to study and analyze pragmatic functions of phraseological units in the headlines of modern British and American newspaper articles. The notion of phraseological unit is revealed and its features are defined. The subject of the study is 185 phraseological units belonging to three groups, namely: phraseological units with a component related to the field of colour, music and weather. The research material includes 9,200 headlines of English newspapers, dated 2014-2018 and selected from the Questia Online Library. Using the method of continuous sampling, we selected phraseological units from the dictionaries The Oxford Dictionary of Idioms, Dictionary of English Idioms & Phrases and McGraw-Hill’s Essential American Idioms Dictionary. In addition, the frequency of use of phraseological units of the three groups in the headlines of British and American discourses was studied and analyzed. The study found that the most common of the three groups was the group of phraseological units with a component related to the field of colour. The second most common is the group of phraseological units with a component related to the field of music, and the least numerous is the group of phraseological units with a component related to the field of weather. In addition, it was determined what phraseological units are the most common in English newspaper headlines and which ones are the least common.
Keywords: фразеологічні одиниці; газетний заголовок; прагматична функція; британські та американські газети